Finish with a sprint: Evidence for time‐selected last leg of migration in a long‐distance migratory songbird. Issue 14 (21st June 2018) - Briedis, Martins; Hahn, Steffen; Krist, Miloš; Adamík, Peter
Abstract: Under time‐selected migration, birds should choose a strategy for outcompeting rivals over securing access to prime resources at the final destination. Thus, migration can be viewed as a race among individuals where winners are arriving first when conditions are suitable. The sprint migration hypothesis predicts that individuals shift from maximum sustained speed to a final burst of sprint to shorten the transition from migration to breeding (Alerstam, 2006). In this study, we test the hypothesis of a final sprint migration in a long‐distance Afro‐Palearctic migrant, the collared flycatcher Ficedula albicollis, during autumn and spring, and compare migration strategies between the seasons. In both seasons, collared flycatchers evidently exhibited sprint migration by increasing their overall speed over the last leg of migration after the Sahara crossing. This phenomenon was more pronounced in spring, contributing to overall faster spring migration and possibly highlighting higher importance for early arrival at the breeding grounds. In both seasons and particularly in spring, late departing individuals flew at a faster rate, partially being able to catch up with their early departing conspecifics. Differential fueling strategies may play an important role in determining migration speed, especially during the early stages of the migration, and might explain the observed differences in migration speeds between late and early departing individuals. Our findings suggest competition for early arrival at the breeding and at the nonbreeding destinations alike. Sprint migration might be an appropriate strategy to gain advantage over conspecifics and settle in prime territories as well as to cope with the increasingly earlier springs at high latitudes. Abstract : In this study, we test the hypothesis of a final sprint migration (Alerstam, 2006) in a long‐distance Afro‐Palearctic migrant, the collared flycatcher Ficedula albicollis . In both seasons, collared flycatchers evidently exhibited a sprint migration by increasing their migration speed over the last leg of the journey. This phenomenon was more pronounced in spring, contributing to overall faster spring migration and possibly highlighting higher importance for early arrival.